Mini Review: Advances in 2-Haloacid Dehalogenases - Wang, Yayue; Xiang, Qiao; Zhou, Qingfeng; Xu, Jingliang; Pei, Dongli (Frontiers in Microbiology, 2021)
2-Haloacid dehalogenases (EC 3.8.1.X) are industrially relevant enzymes that catalyze the cleavage of the carbon-halogen bonds in 2-haloalkanoic acids, releasing halogen ions and producing corresponding 2-hydroxyl acids. The enzymes are fascinating for environmental remediation and green synthesis of optically pure chiral compounds due to their ability to degrade a wide range of halogenated compounds with astonishing efficiency for enantiomer resolution. 2-Haloacid dehalogenases have been extensively studied regarding of their biochemical characterization, protein crystal structures and catalytic mechanisms so far. This review comprehensively reviewed the isolation source, classification, protein structures, reaction mechanisms, biochemical properties and application of 2-haloacid dehalogenases. Also current trends and further development have been included.